Towards a phenomenological conception of experiential justification. - Berghofer, Philipp (Synthese, 2020)
The aim of this paper is to shed light on and develop what I call a phenomenological conception of experiential justification (PCEJ). According to this phenomenological conception, certain experiences gain their justificatory force from their distinctive phenomenology. Such an approach closely connects epistemology and philosophy of mind and has recently been proposed by several authors, most notably by Elijah Chudnoff, Ole Koksvik, and James Pryor. At the present time, however, there is no work that contrasts these different versions of PCEJ. This paper not only bridges this gap, but also reveals problems in current versions of PCEJ. Consequently, I argue for a new version of PCEJ that focuses on what is given within experience and not on how what is given pushes me towards believing something.